Nonsteroidal Anti-inflammatory Drugs for Sciatica: An Updated Cochrane Review. Issue 8 (15th April 2017) - Rasmussen-Barr, Eva; Held, Ulrike; Grooten, Wilhelmus J.A.; Roelofs, Pepijn D.D.M.; Koes, Bart W.; van Tulder, Maurits W.; Wertli, Maria M.
Abstract : Study Design: Systematic review and meta-analysis. Objective: To determine the efficacy of nonsteroidal anti-inflammatory drugs (NSAIDs) on pain reduction, overall improvement, and reported adverse effects in people with sciatica. Summary of Background Data: NSAIDs are one of the most frequently prescribed drugs for sciatica. Methods: We updated a 2008 Cochrane Review through June 2015. Randomized controlled trials that compared NSAIDs with placebo, with other NSAIDs, or with other medication were included. Outcomes included pain using mean difference (MD, 95% confidence intervals [95% CI]). For global improvement and adverse effects risk ratios (RR, 95% CI) were used. We assessed level of evidence using the Grades of Recommendation, Assessment, Development and Evaluation approach. Results: Ten trials were included (N = 1651). Nine out of 10 trials were assessed at high risk of bias. For pain reduction (visual analog scale, 0 to 100) NSAIDs were no more effective than placebo (MD −4.56, 95% CI −11.11 to 1.99, quality of evidence: very low). For global improvement NSAIDs were more effective than placebo (RR 1.14 [95% CI 1.03 to 1.27], low quality of evidence). One trial reported the effect of NSAIDs on disability with very low-quality evidence that NSAIDs are no more effective than placebo. There was low - quality evidence that the risk for adverse effects is higher for NSAID than placebo (RR 1.40, 95% CI 1.02 to 1.93). Conclusion: Our findings show very low-quality evidence that the efficacy of NSAIDs for pain reduction is comparable with that of placebo, low-quality evidence that NSAIDs is better than placebo for global improvement and low-quality evidence for higher risk of adverse effects using NSAIDs compared with placebo. The findings must be interpreted with caution, due to small study samples, inconsistent results, and a high risk of bias in the included trials. Level of Evidence: 1 Abstract : Supplemental Digital Content is available in the text